Who Can Speak and Who Is Heard/Hurt?: Facing Problems of Race, Racism, and Ethnic Diversity in the Humanities in Germany - Motyl, Katharina; Arghavan, Mahmoud; Hirschfelder, Nicole; Kopp, Luvena (transcript, 2019)
Ethnic diversity, race, and racism have been subject to discussion in American Studies departments at German universities for many years. It appears that especially in the past few decades, ethnic minorities and 'new immigrants' have increasingly become objects of scholarly inquiry. Such research questions focus on the U.S. and other traditionally multicultural societies that have emerged out of historical situations shaped by (settler) colonialism, slavery, and/or large-scale immigration. Paradoxically, these studies have overwhelmingly been conducted by white scholars born in Germany and holding German citizenship. Scholars with actual experience of racial discrimination have remained largely unheard.Departing from a critique of practices employed by the German branch of American Studies, the volume offers (self-)reflective approaches by scholars from different fields in the German Humanities. It thereby seeks to provide a solid basis for thorough and candid discussions of the mechanisms behind and the implications of racialized power relations in the German Humanities and German society at large.